2019
DOI: 10.1093/jn/nxz117
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Intake Predicts Weight Loss and Dietary Adherence in Adults Consuming Calorie-Restricted Diets: The POUNDS Lost (Preventing Overweight Using Novel Dietary Strategies) Study

Abstract: Background The effects of dietary composition on weight loss are incompletely understood. In addition to energy intake, fiber intake, energy density, macronutrient composition, and demographic characteristics have all been suggested to contribute to weight loss. Objective The primary aim of this analysis was to assess the role of dietary fiber as a predictor of weight loss in participants who consumed calorie-restricted diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 34 publications
6
57
0
1
Order By: Relevance
“…Out of the 23 studies selected, 14 were secondary analysis of randomized control trials, 8,10,11,13–17,20,24–27,30 nine were intervention studies 9,12,18,23,28,29 and three were cohort studies 19,21,22 …”
Section: Resultsmentioning
confidence: 99%
“…Out of the 23 studies selected, 14 were secondary analysis of randomized control trials, 8,10,11,13–17,20,24–27,30 nine were intervention studies 9,12,18,23,28,29 and three were cohort studies 19,21,22 …”
Section: Resultsmentioning
confidence: 99%
“…In a separate systematic review and meta-analysis of the literature on the effects of viscous fibre ingestion on body weight and composition from 62 trials and 3877 participants, there was a similar significant association with weight loss of −0.33 kg [ 27 ]. Finally, in the ‘Preventing Overweight Using Novel Dietary Strategies’ (POUNDS Lost) study, in 345 participants who consumed a calorie-restricted diet (−750 kcal per day) for 6 months, the most successful predictor of reduction in body weight from a variety of anthropometric and dietary factors was intake of dietary fibre [ 28 ]. Furthermore, dietary fibre was also strongly associated with adherence to the macronutrient prescriptions within the calorie-restricted diets [ 28 ].…”
Section: The Benefits Of Dietary Fibrementioning
confidence: 99%
“…Finally, in the ‘Preventing Overweight Using Novel Dietary Strategies’ (POUNDS Lost) study, in 345 participants who consumed a calorie-restricted diet (−750 kcal per day) for 6 months, the most successful predictor of reduction in body weight from a variety of anthropometric and dietary factors was intake of dietary fibre [ 28 ]. Furthermore, dietary fibre was also strongly associated with adherence to the macronutrient prescriptions within the calorie-restricted diets [ 28 ].…”
Section: The Benefits Of Dietary Fibrementioning
confidence: 99%
“…FV, including legumes and soy products, provide the majority of fiber in recommended healthy diets followed by whole grains and nuts ( Table 1 ). The POUNDS Lost (Preventing Overweight Using Novel Dietary Strategies) study, a randomized trial in 345 adults (54% women; age 5, BMI of 33) found that of all the dietary predictors, fiber had the strongest association with weight loss with an average increase of 3.7 g/day from baseline, lowering weight by −1.4 kg over six months with no significant interactions between fiber intake and diet type, or sex [ 80 ]. In an RCT, 327 young overweight and obese women (mean age 34 years) had a significant increase in daily consumption of fiber by 3.2 g/day, FV by 51.4 g/day, and a decreased intake of meat products, total dietary fat, total energy, and refined carbohydrates [ 81 ].…”
Section: Observational Studiesmentioning
confidence: 99%